1,000 facts about ancient Egypt - Honovich, Nancy (National Geographic kids., 2019)
Presents an illustrated collection of 1,000 facts about ancient Egypt and its geography, religion, rulers, pyramids, occupations, animals, weapons, sphinxes, culture, and demise. Features hundreds of color photographs, a glossary, a timeline, and sources of additional information.